THE ANATOMICAL-MORPHOLOGICAL FEATURES OF OREGANO ORDINARY (ORIGANUM VULGARE L.) WIDLY GROWING IN ARMENIAN FLORA DURING THE PRE-BLOSSOMING PERIOD (Proceedings of the YSU B: Chemical and Biological Sciences, 2021)
The article reports the results of microscopic studies of the oregano leaf in the pre-blossom period. In particular, the following anatomical and morphological features of the oregano leaf during the pre-blossom period were revealed: sinuous cuticle, multicellular simple trichomes, capitate trichomes, stomata, essential oil glands. The latter were located only in the central part, and were absent at the margins. The essential oil glands were of high density mostly in the central part of the raw materials preparation, which were harvested from the regions of dry climatic conditions as opposed to the raw materials harvested from the region of wet climatic conditions. The results of the investigation were definitely conditioned by the climatic features of the regions.
Keywords: Oregano ordinary; standardization; microscopic analysis